HUBUNGAN ANTARA REGULASI EMOSI DENGAN PERILAKU DISIPLIN SANTRI MADRASAH ALIYAH PONDOK PESANTREN QODRATULLAH LANGKAN - Deci Nansi; Fajar Tri Utami (Psikis : Jurnal Psikologi Islami, 2016)
This study aims to investigate the relationship between emotion regulation with discipline. The hypothesis in this study is on the way down there is a relationship between emotion regulation to discipline the students of Madrasah Aliyah boarding school Qodratullah ledge.The population in this study is numbered 563 students which is the total number of students of Madrasah Aliyah boarding school Qodratullah ledge. Sample taken based table Isaac and Michael with a standard error of 10% of the population so samples used are 187 students. Measuring instruments used in this research that use two scales, the first scale that emotion regulation is made with reference to the aspects of emotion regulation raised by Gross and scale of discipline made with reference to the aspects of the discipline proposed by Prijidarminto. Methods of data analysis used to test the hypothesis of the research is Correlation Product Moments. All calculations are done using the computer program SPSS (Statistical Program for Social Science) version 20.00.Based on the analysis of research known 0,000 p where p <0.01 then Ha Ho accepted and rejected. It can be said that there is a positive relationship between emotion regulation to discipline students of Madrasah Aliyah boarding school Qodratullah ledge. This can be seen in the analysis of the results of data analysis showed a correlation coefficient (r) indicates the value of 0.329 with significance (p) of 0.000 or p <0.01.